The Effectiveness of Visual Communication Design in Universitas Terbuka’s Social Media Promotion for Attracting Gen Z - Rahadian Kamandaru (Institut Seni Indonesia Yogyakarta, 2025)
This study examines the effectiveness of visual communication design in Universitas Terbuka's (UT) social media promotion strategy to attract Gen Z prospective students. This study stems from the increasing role of social media as the primary communication channel for educational institutions in the context of digital visual culture. Using a mixed methods approach, the study combines quantitative analysis of Gen Z preferences and perceptions through online surveys and qualitative analysis through interviews with UT's central and regional marketing teams. The results show that visual design elements such as the dominant blue-yellow color scheme, modern sans-serif typography, and short video content format (reels) significantly influence the engagement level of young audiences. However, a gap was also found between the visual imagery developed by UT and Gen Z's digital aesthetic expectations, particularly regarding color variation, typographic consistency, and the response speed of UT's social media administrators. This study emphasizes the importance of implementing a visual communication strategy based on the visual culture of the digital generation and the continuity of visual messages across platforms. These findings are expected to serve as a reference for higher education institutions in designing digital promotions that are effective, engaging, and relevant to Gen Z's characteristics.